Erythrocyte Changes in Death after General Over Cooling - Revo Z. Alekseev (Journal of Global Pharma Technology, 2020)
In medicine, the problems of hypothermia and body ‘revitalization’ remain open. Insufficient knowledge of the mechanisms of dying at ultralow temperatures gives grounds to supplement the idea of the cellular-molecular mechanisms of deadly hypothermia. The aim of this study was to assess the morphology of red blood cells during fatal hypothermia at extremely low temperatures (i.e. below -40°C) using atomic force and scanning electron microscopy, high resolution JSM-7800F. The subject of the study was blood smears of people who died from hypothermia and from a gunshot wound. In a man who died of hypothermia at extremely low temperatures (i.e. -42°C), whose smear was taken within 1 day, red blood cells were characterized by minimal changes than when dying from a gunshot wound. The discocytic form of erythrocytes with a flat surface was preserved; however, we found an increase in the depth of the central concavity of red blood cells, which may be associated with an increase in the volume of red blood cells. It was found that even a slight difference in the temperature of the body regions (i.e. ∆ 2.4°C) at the time of blood sampling affects the ratio of different forms of red blood cells after complete thawing. The lower the temperature, the more degenerative forms of red blood cells appear. After complete thawing of the corpse on the 4th day, all red blood cells (100%) had a different degree of dysmorphism, a more flattened surface, an increase in diameter and heterogeneity and roughness of the plasma, indicating signs of hemolysis. Keywords: Red blood cells; Death from hypothermia; Atomic microscopy; Scanning electron microscopy.